EFFECTS OF SELF-CONFIDENCE AND PEER CONFORMITY ON STUDENTS’ CHEATING BEHAVIOR - Hanifah, Faizah; Khosiin, Khamam; Khoiriyah, Khoiriyah (Yayasan Adra Karima Hubbi, 2025)
This study investigates the influence of self-confidence and peer conformity on students’ cheating behavior in Islamic Religious Education at SMA Muhammadiyah Tanjung Redeb. Using a quantitative correlational design, data were collected from 79 students selected through simple random sampling from a population of 357 students. Self-confidence, peer conformity, and cheating behavior were measured using validated and reliable Likert-scale questionnaires, and the data were analyzed using multiple linear regression after meeting classical assumption tests. The results indicate that both self-confidence and peer conformity have significant partial effects on cheating behavior, with self-confidence (? = 0.438, p = 0.005) and peer conformity (? = 0.316, p = 0.047) showing positive relationships. Simultaneously, these two variables significantly predict cheating behavior (F = 11.555, p < 0.001) and explain 23.3% of the variance in students’ cheating tendencies (R² = 0.233). The novelty of this study lies in its integration of psychological and social factors within the specific context of Islamic Religious Education, highlighting how internal self-beliefs and peer dynamics interact to shape academic integrity. These findings imply that educational interventions should not only strengthen students’ self-confidence but also cultivate healthy peer norms and social awareness to effectively reduce cheating behavior and promote ethical learning practices.